2021
DOI: 10.2478/jtim-2021-0038
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning of fungal-based peptides as modulators of angiotensin-converting enzyme-related carboxypeptidase, SARS-coronavirus HR2 domain, and coronavirus disease 2019 main protease

Abstract: Background and Objectives Angiotensin-converting enzyme-related carboxypeptidase, SARS-Coronavirus HR2 Domain, and COVID-19 main protease are essential for the cellular entry and replication of coronavirus in the host. This study investigated the putative inhibitory action of peptides form medicinal mushrooms, namely Pseudoplectania nigrella, Russula paludosa, and Clitocybe sinopica, towards selected proteins through computational studies. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Several studies have revealed that mushroom protein has the potential to be used control pathogenic microbes and other human diseases. Peptides derived from Pseudoplectania nigrella , Russula paludosa , and Clitocybe sinopica exhibited binding affinity and the ability to modulate the flexibility and stability of selected coronavirus proteins, including ACE-related carboxypeptidase, SARS-Coronavirus HR2 Domain, and COVID-19 main protease [ 82 ]. Nowadays, the hepatoprotective effects of polysaccharide-peptides from mushrooms have been evaluated against nonalcoholic fatty liver disease (NAFLD).…”
Section: Other Bioactivitiesmentioning
confidence: 99%
“…Several studies have revealed that mushroom protein has the potential to be used control pathogenic microbes and other human diseases. Peptides derived from Pseudoplectania nigrella , Russula paludosa , and Clitocybe sinopica exhibited binding affinity and the ability to modulate the flexibility and stability of selected coronavirus proteins, including ACE-related carboxypeptidase, SARS-Coronavirus HR2 Domain, and COVID-19 main protease [ 82 ]. Nowadays, the hepatoprotective effects of polysaccharide-peptides from mushrooms have been evaluated against nonalcoholic fatty liver disease (NAFLD).…”
Section: Other Bioactivitiesmentioning
confidence: 99%
“…COVID-19 is an infectious disease caused by SARS-CoV-2. [ 10 , 11 , 12 , 13 ] Most people infected with the virus will experience mild-to-moderate respiratory illness. [ 14 , 15 ] However, some will become seriously ill and require medical attention.…”
Section: Discussionmentioning
confidence: 99%
“…3. The trajectories indicate distinct differences and variations in the dynamic motions of the components of BSA required for biological function between the two complexes [45]. The RMSD which is the measure of the average distance between the atoms (usually the backbone atoms) revealed the structural stabilities of BSA complexes with glucose and quercetin.…”
Section: Molecular Dynamics Studies For Bsa Docked With Glucose and Q...mentioning
confidence: 99%